2001
DOI: 10.1074/jbc.c100273200
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome Calcium Channel β Subunits

Abstract: Schistosomes are parasitic flatworms that cause schistosomiasis, a major tropical disease. The current drug of choice against schistosomiasis is praziquantel (PZQ), which has minimal side effects and is potent against all schistosome species. The mode of action of PZQ is unknown, though the drug clearly affects Ca 2؉ channel ␣ 1 subunit results in a striking reduction in current amplitude. In the case of Ca v 2.3, this current reduction can be partially reversed by addition of 100 nM PZQ, which results in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 14 publications
0
52
0
1
Order By: Relevance
“…Diverse studies have focused on the phenomenon (Table 3). Initially, it was hypothesized that PZQ1 affects Ca 2ϩ influx through voltage-operated calcium channels (67)(68)(69)(70)(71)(72)(73). However, in subsequent studies, it was shown that calcium accumulation by itself, as measured in parasites maintained in vitro, may not explain the schistosomicidal activity of PZQ1 (71,72).…”
Section: How Does Pzq Kill Schistosomes?mentioning
confidence: 99%
“…Diverse studies have focused on the phenomenon (Table 3). Initially, it was hypothesized that PZQ1 affects Ca 2ϩ influx through voltage-operated calcium channels (67)(68)(69)(70)(71)(72)(73). However, in subsequent studies, it was shown that calcium accumulation by itself, as measured in parasites maintained in vitro, may not explain the schistosomicidal activity of PZQ1 (71,72).…”
Section: How Does Pzq Kill Schistosomes?mentioning
confidence: 99%
“…In contrast, the schistosome cytoplasmic ␤ subunits express robustly in mammalian cells (11) and in Xenopus oocytes (8). The less conventional of the two ␤ subunits has unusual structural and functional properties and appears to be involved in the action of praziquantel (8). In contrast, less data are available for the more conventional schistosome ␤ subunit, which does not appear to play a role in praziquantel action.…”
mentioning
confidence: 90%
“…Perhaps ␤ Sm represents one of these mechanisms, working to reduce Ca 2ϩ influx by increasing the rate of Ca v channel inactivation (and decreasing current density). The second, "variant" schistosome ␤ subunit also appears to dampen Ca 2ϩ currents (8). Additionally, it is known that schistosomes express a variety of Ca 2ϩ -buffering proteins.…”
Section: Volume 285 • Number 46 • November 12 2010mentioning
confidence: 99%
See 2 more Smart Citations